KAJIAN ISU KONTEMPORER DALAM ISLAM MELALUI MEDIA DIGITAL: STUDI HADIS TENTANG ONLINE SHOP - Tilawati, Anis (Mazalat: Jurnal Pemikiran Islam, 2023)
The contemporary issue raised in this article is related to the online shop phenomenon. Where it is ingrained in the daily activities of today's society. The point of view highlighted by the researcher is more on the way Muslims react to it, which starts with exploring the online shop law in Islam. Rather than that, in this digital era, it is not surprising that the majority of Muslim communities are interested in using digital media to study religion instantly. Media Youtube for example, a video that examines the online shop from the perspective of hadith. How is the credibility of digital media in studying contemporary issues in Islam? And how does the Hadith study talk about online shops? Then what is the relationship between these two problems? Researchers try to answer all these problems using field and library research methods. The findings include that the study of hadiths about online shops through digital media can be easily understood but the discussion is not detailed enough. As for the hadith, this matter can be correlated with the law of buying and selling which is prescribed by law.